Diagnostic value of a guaiac occult blood test and faecal alpha 1-antitrypsin. Issue 1 (January 1995) - Moran, A; Husband, D; Jones, A F; Asquith, P
Abstract : This study evaluates the diagnostic accuracy of a faecal occult blood test and faecal alpha 1-antitrypsin in the investigation of patients with gastrointestinal symptoms or iron deficiency anaemia. One hundred and seventy nine patients with either iron deficiency anaemia (n = 67), changed bowel habit and aged > 39 years (n = 107), or a history suggestive of melaena (n = 5) provided faecal samples. After investigation, 32 patients had a diagnosis of possible gastrointestinal bleeding and 139 patients had no evidence of gastrointestinal bleeding. Eight patients had a cause of enteric protein loss in the absence of gastrointestinal bleeding and were excluded from subsequent analysis. The faecal alpha 1-antitrypsin test was diagnostically more accurate than the guaiac test in identifying probable gastrointestinal bleeding (82% and 72% respectively, p < 0.05). This faecal alpha 1-antitrypsin test was also more specific (83% and 72% respectively, p < 0.05), but was not significantly more sensitive (78% and 72% respectively). The sensitivity of these tests was insufficient to recommend their use for most patients in this study.